2018
DOI: 10.1186/s40425-018-0346-6
|View full text |Cite
|
Sign up to set email alerts
|

Immune-checkpoint inhibitor-induced diarrhea and colitis in patients with advanced malignancies: retrospective review at MD Anderson

Abstract: BackgroundImmune checkpoint inhibitors (ICPIs) are gaining increasing popularity as an efficacious treatment for advanced malignancies. ICPI treatment can be complicated by diarrhea and colitis. Systemic steroids are the first line treatment. Infliximab is reserved for severe refractory cases. We aimed to assess the impact of ICPI-induced diarrhea and colitis and their immunosuppressive treatment on patients’ outcomes.MethodsThis retrospective analysis was conducted in 327 cancer patients who received ICPIs be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
176
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(184 citation statements)
references
References 32 publications
6
176
2
Order By: Relevance
“…When the relationship between the occurrence of nivolumab‐induced irAEs and nivolumab efficacy was analyzed by irAE category, the occurrence of rash, endocrine disorders, and gastrointestinal toxicity was correlated with the ORR to nivolumab. The occurrence of these three toxicities has previously been correlated with the efficacy of anti‐PD‐1 antibodies, and the present data appear to support these findings.…”
Section: Discussionsupporting
confidence: 88%
“…When the relationship between the occurrence of nivolumab‐induced irAEs and nivolumab efficacy was analyzed by irAE category, the occurrence of rash, endocrine disorders, and gastrointestinal toxicity was correlated with the ORR to nivolumab. The occurrence of these three toxicities has previously been correlated with the efficacy of anti‐PD‐1 antibodies, and the present data appear to support these findings.…”
Section: Discussionsupporting
confidence: 88%
“…In a retrospective series that included 75 patients who had immune‐related enterocolitis, infliximab use was associated with a shorter time to symptom resolution and shorter duration of steroid use, and there was no decrease in overall survival . In another retrospective series, which included 117 patients treated with ICI who developed diarrhea, a steroid duration >30 days was associated with higher rates of infection compared with a shorter duration of steroid use with or without infliximab . In a retrospective series of the endoscopic and histologic features of ICI‐induced colitis, patients with ulcerations on colonoscopy were more likely to have steroid‐refractory colitis …”
Section: Checkpoint Inhibitorsmentioning
confidence: 98%
“…43 In another retrospective series, which included 117 patients treated with ICI who developed diarrhea, a steroid duration >30 days was associated with higher rates of infection compared with a shorter duration of steroid use with or without infliximab. 44 In a retrospective series of the endoscopic and histologic features of ICI-induced colitis, patients with ulcerations on colonoscopy were more likely to have steroid-refractory colitis. 45 Vedolizumab, an anti-integrin α4β7 antibody with gut-specific effects, has been investigated for patients with steroid-dependent or refractory ICI-induced colitis.…”
Section: Dermatologic Toxicitymentioning
confidence: 99%
“…In patients with inadequate or no response to corticosteroids, dose escalation of steroids in time, and upgrading treatment to infliximab (IFX) or vedolizumab when necessary is recommended. Studies have shown that compared with long‐term steroid treatment, the therapy of short‐term steroids plus IFX reduces the risk of various opportunistic infections . Fecal microbiota transplant is reported to be valid in cases with GI irAEs refractory to steroids, IFX or vedolizumab …”
Section: Gastrointestinal Toxicity Of Icismentioning
confidence: 99%
“…Studies have shown that compared with long-term steroid treatment, the therapy of short-term steroids plus IFX reduces the risk of various opportunistic infections. 17 Fecal microbiota transplant is reported to be valid in cases with GI irAEs refractory to steroids, IFX or vedolizumab. 18…”
Section: Managementmentioning
confidence: 99%